Determinants of competitiveness of agriholdings and independent farms in Ukrainian arable production - Simon Walther (Johann Heinrich von Thünen-Institut, 2014)
Agriholdings are large horizontally and/or vertically integrated corporate farming businesses which are characterized by having multiple operations under a central management. This organizational form has been developing in Kazakhstan, Russia and Ukraine since the late 1990s and has since then gained a considerable market share, especially in arable production. Ukraine is one of the three countries in which the development of agriholdings was very pronounced. While the competition for arable land in Ukraine has been weak so far, it is expected to increase in the future. In order to be able to assess whether agriholdings or independent farms will then be more competitive on the land market also under changing conditions, (a) competitive advantages and disadvantages of the two organizational forms in Ukrainian arable production are identified in this thesis, (b) their impact on competitiveness is quantified, and (c) likely future adaptations of both organizational forms in order to maintain or increase their competitiveness are explored. – – Agrarholdings sind große horizontal und/oder vertikal integrierte Agrarunternehmen, die sich dadurch auszeichnen, dass sie mehrere landwirtschaftliche Produktionseinheiten unter einer zentralen Verwaltung haben. Diese Organisationsform hat sich in Kasachstan, Russland und der Ukraine seit den späten 1990er-Jahren entwickelt und hat seitdem insbesondere im Ackerbau einen erheblichen Marktanteil erreicht. Die Ukraine ist eines dieser drei Länder, in dem die Entwicklung von Agrarholdings besonders ausgeprägt vonstatten ging. Wenngleich der Wettbewerb um Ackerland in der Ukraine bisher schwach ausgeprägt war, wird erwartet, dass dieser in der Zukunft zunehmen wird. Um einschätzen zu können, ob dann Agrarholdings oder Einzelbetriebe auch unter sich ändernden Bedingungen eine höhere Wettbewerbsfähigkeit auf dem Landmarkt besitzen werden, werden in dieser Arbeit (a) Wettbewerbsvor- und -nachteile der beiden Organisationsformen im ukrainischen Ackerbau identifiziert, (b) deren Auswirkungen auf die Wettbewerbsfähigkeit quantifiziert und (c) Zukunftsanpassungen, die beide Organisationsformen wahrscheinlich unternehmen werden, um ihre Wettbewerbsfähigkeit zu erhalten oder zu verbessern, untersucht.
urn:nbn:de:gbv:253-201403-dn053389-9
Keywords: 630